Micro-Needle with Polygonal Structure of MicroChannel for Stress and Blood or Drug Flow Optimization - Mohd Danial, Ibrahim; Yana Shaheera, Yunos; Nobuo, Watanabe; Nur Alia Athirah, Mohtadzar; Siti Noor, Haizum Semait; Andrew Ragai, Henry Rigit; Yuta, Sunami; Kuwang, Wong Lee; Mohd Rahmat, A Rahman; Muhammad Zaidi, Mohtar (Faculty of Engineering, Chulalongkorn University, 2017)
This paper presents micro-needle with different tip and inner structure of the needle for optimizations of pain stresses and drug or blood deliveries. The micro-needle comes with several design’s parameters of length ranging from 5mm to 50mm and diameter ranging from 100µm to 200µm. A hollow micro-needle with four different tip designs which are 10°, D3-2, D6 and Quadruple are also designed to optimize the pain stresses parameters. In order to improve the flow deliveries, the inner structure of the channel is modified into various polygonal shape which is square, hexagon and dodecagon. It shows that, having less contact surface area between the skin and micro-needle’s tip and polygonal shape of inner channel has better performance for both of the objectives. These feasible region of average velocity and stress of the micro-needle have satisfied in determining the best design for tip and inner channel of the micro-needle under certain conditions and constraints. The three-dimensional geometry study had improved the insertions performance and efficiencies in painless drug or blood deliveries.